(untitled) (REMUNOM, 2025)
Depression is a psychiatric disorder characterized by transient mood changes without reason or disproportionate to the cause. During adolescence, several physiological changes occur that can lead to the transformation of a normal adolescent process into a pathological case. In this regard, according to the most recent articles, it is seen that adolescents who present a depressive condition express important phenomenological characteristics, such as irritability and instability, presenting episodes of outbursts and anger, but usually do not show sadness. In addition, boys report feelings of contempt and challenges, while girls report sadness, anxiety and concern about popularity. The therapeutic approach in adolescents is still a subject of questions, but evidence shows that cognitive-behavioral therapy and interpersonal therapy present significant clinical improvement in patients in addition to the use of antidepressants, usually serotonin inhibitors.